Performance Evaluation of Handover using A4 Event in LEO Satellites Network - Yu, Jina; Lee, Wonjae; Kim, Jae Hyun (APWCS 2022 - 2022 IEEE VTS Asia Pacific Wireless Communications Symposium, 2022)
Low earth orbit (LEO) satellites have fast mobility, which causes frequent handover (HO) problems. Solving the matters of HO is very important for a seamless and stable service connection. Therefore, in this paper, to overcome the HO issues in LEO we used A4 event which is discussing in 3rd generation partnership project (3GPP). Unlike the terrestrial network, in non-terrestrial network (NTN), the difference between reference signal received power (RSRP) of cell edge and RSRP of cell center is very small. For this reason, 3GPP has been discussing the method comparing the RSRP of cells with an absolute threshold rather than comparing the RSRP of the serving cell and the neighboring cell in HO events. In addition, we compare the HO performance of A3 event based HO and A4 event based HO according to L3 filter K value. The simulation results indicate that radio link failure (RLF) and handover failure (HOF) perform better in A4 event based HO than A3 event based HO. In addition, the performance of RLF and HOF performs significantly better when L3 filter K value is 0 than 6, and 13.
Keywords: 3rd generation; Earth orbits; Event-based; Hand over; Low earth orbit; Low earth orbit satellites; Mobility management; Received power; Reference signals; Satellite communications; Handover; Low earth orbit (LEO); Mobility management; Satellite communications